Seguimiento distribuido del punto de máxima potencia en micro-redes eólicas - Ramos-Paja, Carlos Andrés; Saavedra-Montes, Andrés Julian; Arango Zuluaga, Eliana Isabel (Ingeniería, 2012)
With the aim of reducing the hardware requirements in micro-grids based on wind generators, a distributed maximum power point tracking algorithm is proposed. Such a solution reduces the amount of current sensors and processing devices to maximize the power extracted from the micro-grid, reducing the application cost. The analysis of the optimal operating points of the wind generator was performed experimentally, which in addition provides realistic model parameters. Finally, the proposed solution was validated by means of detailed simulations performed in the power electronics software PSIM, contrasting the achieved performance with traditional solutions.